2021
DOI: 10.1590/0037-8682-0530-2020
|View full text |Cite
|
Sign up to set email alerts
|

Residual foci of Triatoma infestans infestation: Surveillance and control in Rio Grande do Sul, Brazil, 2001-2018

Abstract: Introduction: This retrospective study conducted from 2001 to 2018 investigated the residual foci of Triatoma infestans infestation in Rio Grande do Sul, Brazil. Methods: The data were obtained via entomological surveillance and the distribution of vector occurrence. The coverage of active research was mapped. Results: The largest coverage rate for active research was observed in the northwest region of the total of 515,081 domiciles researched. Most T. infestans specimens were captured in the peridomicile. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
1
7
0
1
Order By: Relevance
“…The study carried out by Almeida et al 20 showed the increasing frequency of T. rubrovaria in rural households in Southeastern RS State and stated these authors claimed that this species may be invading areas that had been previously occupied by T. infestans , the main domestic CD vector which was eliminated in the State by chemical control 11 , corroborating the findings of this study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The study carried out by Almeida et al 20 showed the increasing frequency of T. rubrovaria in rural households in Southeastern RS State and stated these authors claimed that this species may be invading areas that had been previously occupied by T. infestans , the main domestic CD vector which was eliminated in the State by chemical control 11 , corroborating the findings of this study.…”
Section: Discussionsupporting
confidence: 87%
“…Although T. infestans has been eliminated in RS State, there are other triatomine species that persist in rural households 11 . Therefore, this study aimed at evaluating the occurrence of CD vectors based on the main species captured in Southern RS, from 2008 to 2019.…”
Section: Introductionmentioning
confidence: 99%
“…50 , 121 As with R. prolixus in Mexico, 16 however, a few T. infestans residual foci have since been detected in Brazil, again underscoring the need for long-term surveillance. 122 , 123 , 124 , 125 Non-native T. infestans have also proven difficult to control in urban Arequipa, Peru. 126 , 127 Importantly, moreover, T. infestans is native, and hence widespread in wild environments, across the dry Chaco (Argentina, Paraguay and Bolivia) and the inter-Andean temperate-dry valleys of south-eastern Bolivia.…”
mentioning
confidence: 99%
“…Triatoma infestans, a species that is better adapted to households, is regarded as the main vector of CD. However, even though this vector was eliminated from southern RS, other species of triatomines have persisted in rural houses 3,4,5 .…”
mentioning
confidence: 99%